Studies on Morphology of Medial Cuneate Nucleus in Buffalo (Bubalus bubalis) - N.M, Rajashailesha. (Indian Journal of Veterinary Anatomy, 2020)
The morphology of medial cuneate nucleus of the buffalo has been described by materials collected from eight buffalos. Serial and semi serial sections of brain stem were stained with nissl and myelin stain. The medial cuneate nucleus in the buffalo extended from a level slightly rostral to the caudal pole of the nucleus gracilis to the level of the caudal pole of the medial vestibular nucleus. The nucleus appeared as a dorsomedial bulge from the dorsal surface of the central gray into the substance of fasciculus cuneatus in its caudal pole and rostrally nucleus enlarged in size and presented a roughly triangular to rectangular at the caudal pole of the lateral cuneate nucleus in transverse sections. In Rhesus monkey medial cuneate nucleus having triangular portion and a round portion which could not be identified in the buffalo. The average length of the medial cuneate nucleus in the buffalo was 19.8 mm. The average maximum width and height nucleus was 1.47 mm. and 1.5 mm respectively. The average height of the nucleus exceeded width by 0.3 mm.